DEVELOPING THE 2024 CATALOGUE OF TRADITIONAL MEDICINE TREATMENT PROTOCOLS FROM HIS DATA (2022-2023) AND EVALUATING THEIR COVERAGE IN RELATION TO OUTPATIENT MORBIDITY PATTERNS AT THE PROVINCIAL LEVEL (Vietnam Journal of Community Medicine, 2026)
Objective: To develop a 2024 catalogue of traditional medicine treatment protocols based on real-world utilization and to quantify coverage relative to the provincial outpatient morbidity profile.Methods Retrospective cross-sectional study using hospital information system (HIS) data from the Traditional Medicine Department, Tien Giang provincial General Hospital (January 2022 to December 2023). Data were cleaned; principal vs. comorbid diagnoses were distinguished from HIS diagnosis fields; and ICD-10-to-protocol mapping was applied. Frequencies and percentages of protocol use were tabulated. The 2024 list was constructed under a KEEP-NEW-RETIRE framework. Coverage for principal and comorbid conditions was calculated as the sum of proportions of protocols in the KEEP group divided by the sum of proportions of all protocols with historical utilization data.Results: Four highly utilized protocols were KEPT (M17, I69.3, K29, M10). The 2024 catalogue includes 10 principal-diagnosis protocols and 3 comorbidity protocols; NEW items mainly cover musculoskeletal/rehabilitation and digestive-metabolic conditions. Coverage reached 96.6% for principal diagnoses (23.34/24.15) and 95.0% for comorbid diagnoses (19.04/20.05). RETIRED protocols accounted for very low shares (≤ 1%).Conclusion: The HIS-informed list achieves very high coverage, streamlines low-use items, and addresses gaps along two priority axes. This approach is appropriate for provincial settings and provides a foundation for workflow standardization, adherence monitoring, and pre-post evaluation.
Keywords: Traditional medicine, treatment protocols, HIS, morbidity profile, service coverage.